Elementary Particles of the Capitalist Mode of Power - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2006)
Theories of society, as of nature, are characterized by their elementary particles. The elementary particle of neoclassical economics is the util. The elementary particle of classical Marxism is abstract labour. These elementary particles represent material quanta. They are deemed useful because both neoclassical economics and classical Marxism analyze capitalism as a mode of production and consumption. In this paper we offer a different approach. We argue that, most broadly, capitalism should be seen not as a mode of production, but a mode of power. From a viewpoint of power, utils and abstract labour are useless. They represent absolute magnitudes, whereas power is inherently relative. To understand the capitalist mode of power we need new elementary particles. The basic unit of analysis we begin with is differential capitalization. Capitalization represents the present value of expected future earnings (ex-post future earnings modified by investors' hype), which in turn are corrected for risk perceptions and discounted by the normal rate of return. Differential capitalization benchmarks the capitalization of any owner or group of owners against the average owner. The paper begins by exploring the four elementary particles that comprise differential accumulation – future earnings, hype, risk and the normal rate of return. It concludes by assessing the implications of this new framework of differential capitalization for understanding the capitalist mode of power.
Conference: Sixth International Conference of Rethinking Marxism. University of Massachusetts, Amherst. October 2006
Keywords: 330; capital; capitalization; hype; labour; Marxism; neoclassical economics; normal rate of return; risk; power; profit; utility; value